Odpowiedzi

2010-03-28T20:47:00+02:00
A)
(x-2)^2-2(x-2y)=1-(3-x)(3+x)
2x+y=4

x^2-4x+4-2x+4y=1-3^2+x^2
2x+y=4

x^2-4x-2x+4y-x^2 =1-9-4
2x+y=4

-6x+4y=-12
2x+y=4 /*3

-6x+4=-12
6x+3y=12

7y=0 /: 7
y=0

2x+0=4
y=0

2x=4 /:2
y=0

x=2
y=0

b)
(x+1)^2 +y^2-8=(y-2)^2+(x-3)(x+3)
3x-y+4=0

x^2+2x+1+y^2-8=y^2-4y+4+x^2-9
3x-y=-4

x^2+2x+y^2-y^2+4y-x^2=-9-1+8+4
3x-y=-4 /*4

2x+4y=2
12x-4y=-16

14x=-14 /:14
x=-1

2*(-1)+4y=2
x=-1

-2+4y=2
x=-1

4y=2+2
x=-1

x=-1
y=1

c)
(x-1)^2-(y-3)^2=(x-y)(x+y)
x+y/2-y+4/3=1 /*6

x^2-2x-y^2+6y-x^2+y^2=-1+9
3x+3y-2y-8=6

-2x+6y=8
3x+y=14 /: (-6)

-2x+6y=8
-18x-6y=-84

-20x=-80 /: (-20)
x=4

-2*4+6y=8
x=4

-8+6y=8
x=4

6y=8+8
x=4

6y=16 /:6
x=4

y=2 i 2/3
x=4

d)
(y+1)^2-x(4x+5)=(y+2x)(y-2x)
3x-y=1

y^2+2y+1-4x^2-5x=y^2-(2x)^2
3x-y=1

y^2+2y+1-4x^2-5x=y^2-4x^2
3x-y=1

2y-5x=-1
3x-y=1 /*2

2y-5x=-1
-2y+6x=2

x=1

-2y+6*1=2
x=1

-2y=2-6
x=1

x=1
y=2

e)
(x-3)^2-(x-5)(x+5)=2y+48
x+y/2 - x-y/4=3/4 /*4

x^2-6x+9-x^2+25=2y+48
2(x+y)-x-y=3

x^2-6x-x^2-2y=48-9-25
2x+2y-x-y=3

-6x-2y=14
x+y=3 /*2

-6x-2y=14
2x+2y=6

-4x=20/: (-4)
x=-5

2*(-5)+2y=6
x=-5

-10+2y=6
x=-5

2y=6+10
x=-5

x=-5
y=8

f)
(x+1)^2-2y-12=(x-3)(x+3)
3x-y=-4

x^2+2x+1-2y-12=x^2-9
3x-y=-4

x^2+2x-2y-x^2=-9-1+12
3x-y=-4

2x-2y=2
3x-y=-4 /*(-2)

2x-2y=2
-6x+2y=8

-4x=10 /: (-4)
x=2,5

2*2,5-2y=2
x=2,5

5-2y=2
x=2,5
-2y=2-5
x=2,5

x=2,5
y=1,5